2011
DOI: 10.1021/jo102432a
|View full text |Cite
|
Sign up to set email alerts
|

To Bend or Not to Bend! The Dilemma of Allenes

Abstract: Allenes, though expected to be linear, are found to be bent in many examples, especially in the case of cyclic allenes. The bending of allene is attributed to the weakening of π-bond strength across the allene. However, tetrakis(dimethylamino)allene {((CH(3))N)(2)C═C═C(N(CH(3))(2))}, which is characterized by push-push interactions, has been shown to be linear, thus leading to doubts of the current understanding of the bent allenes. In this article, we report the ab initio MO/DFT, NBO based electronic structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 77 publications
3
51
0
Order By: Relevance
“…5 However, we note that the description with two dative bondsthus two carbene lone pairs bonding to a nitrogen cationis arbitrary and a description with two electron sharing bonds and a nitrogen anion is at least equally justied or even more justied because it assigns the negative charge to the electronegative nitrogen atom and positive charges to the carbon atoms. 2 The small energy differences between these structures are in line with a fairly low double-bond character. 14 kJ mol À1 for the carbodicarbene in Scheme 1 calculated at the BP86/TZ2P level of theory).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…5 However, we note that the description with two dative bondsthus two carbene lone pairs bonding to a nitrogen cationis arbitrary and a description with two electron sharing bonds and a nitrogen anion is at least equally justied or even more justied because it assigns the negative charge to the electronegative nitrogen atom and positive charges to the carbon atoms. 2 The small energy differences between these structures are in line with a fairly low double-bond character. 14 kJ mol À1 for the carbodicarbene in Scheme 1 calculated at the BP86/TZ2P level of theory).…”
Section: Introductionmentioning
confidence: 78%
“…2 Aliphatic or aromatic groups favour the 2-azaallenium form. 1 According to quantum chemical MP2/6-31G*//4-31G calculations on the parent compound [N(CH 2 ) 2 ] + (R 1 ¼ R 2 ¼ H), the bent-planar 2-azaallylium form is 176 kJ mol À1 higher in energy than the linear orthogonal 2-azaallenium form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Patel and Bharatam demonstrated that their geometry, linear (formally of the allene type) or bent (formally of the E(0) type), strongly depends on the nature of the substituents. 28 This finding can be illustrated by phosphines and heteroatomstabilized carbene ligands that have strong -donor, and weak -acceptor properties. These ligands weaken the -bonds in allene-like structures and consequently favor a bent structure with donor-acceptor bonds.…”
Section: Introductionmentioning
confidence: 99%
“…PAs obtained in our study exceed well above previously calculated 15 values for allenes. 8,17,18 Analysis of results obtained by DFT calculations reveals that the fusion of five and seven-member rings leads to increased basicity by better delocalization of positive charge upon protonation. The enhanced basicity of 1,1spiroalkylated azulenoallene 3 is attributed in the literature 19 to 20 the stabilization of both the inductive and σ-π conjugation effects of the exocyclic ring at the 1-position and the π-π conjugation of the double bond at the 2,3-positions in respective 1H-azulenium cation.…”
mentioning
confidence: 99%